Kepekaan Filologis untuk Pengkajian Budaya - Bernard Arps (Masyarakat Pernaskahan Nusantara, 2020)
The author argues for the importance of a scholarly attitude and competence he terms philological sensitivity. Philology is usually associated with the study of manuscripts, where it is a sophisticated approach for making sense of texts. It entails a specific focus and mode of understanding. But the significance and utility of philology are not restricted to texts or manuscripts. Its scope is wider. Its approach is grounded in a cultural tendency that lives in society, namely the tendency to experience and try to understand five aspects of a cultural process or object: its artefactuality, apprehensibility, compositionality, contextuality, and historicity. If cultivated to meet the requirements of academic scholarship, this philological sensibility may form a perspective for understanding other kinds of artefacts too – especially if selectively enriched with elements from philological traditions worldwide. The author discusses examples from his own research: a manuscript with the narrative of Amir Hamza in Javanese, religious sermons in Osing on Youtube, and oral critique regarding shadow puppetry. === Penulis mengemukakan pentingnya sebuah sikap dan keterampilan ilmiah yang disebutnya kepekaan filologis. Filologi lazim dihubungkan dengan studi naskah tulisan tangan, di mana filologi merupakan pendekatan canggih untuk mengapresiasi teks. Pendekatan tersebut membawa fokus dan cara pemahaman yang khas. Tetapi makna dan guna filologi tidak terbatas pada teks, apalagi naskah. Jangkauannya lebih luas. Pendekatan yang telah dikembangkan dalam rangka filologi teks itu berdasarkan kecenderungan kultural yang hidup di masyarakat, yaitu kecenderungan untuk menghayati dan memahami lima aspek dari sebuah proses atau benda budaya: keterbuatan, ketercerapan, ketersusunan, kontekstualitas dan kesejarahannya. Jika dipupuk sehingga memenuhi syarat ilmu pengetahuan, sensibilitas filologis tersebut bisa menjadi wawasan yang andal untuk pemahaman artefak budaya lain pula – apalagi kalau wawasan tersebut diperkaya dengan menyerap unsur-unsur terpilih dari tradisi filologi seantero dunia. Penulis mengutip contoh dari penelitiannya sendiri: naskah berisi ceritera Amir Hamzah berbahasa Jawa, ceramah agama Islam berbahasa Osing di Youtube, dan kritik lisan atas pertunjukan wayang.